Development of Instruments of The System of Financial and Credit Support of The Agroindustrial Complex in The Activities of Russian Agricultural Bank - Nataliya ALEKSEEVA; Lyudmila KORNILOVA; Andrey VALERIANOV; Tatiana MEDVEDEVA; Artur SEMENOV; Maria TOLSTOVA (Communications of International Proceedings, 2021)
The article provides an overview and systematization of directions and tools used in banking to support and provide modern services to enterprises in the agro-industrial complex. Since Russian Agricultural Bank plays a decisive role in banking services for agriculture and in the banking sector of the Russian Federation as a whole, this study was carried out on the basis of its reporting data. The conclusion was the conclusion about the extreme importance of implementing an integrated approach in the development of tools for the system of financial and credit support of the agro-industrial complex in activities, which should involve the individualization of traditional and the development of new products not only in investment and credit, settlement and deposit areas of banking services, but also modern remote products, including using artificial intelligence technologies. The result of the study is the identification of the most promising directions for the development of banking services, which will provide an effective mechanism for servicing and expanding the client base, the introduction of promising products that determine the innovativeness of the bank's activities, as well as solving the problems of developing the agro-industrial complex.
Keywords: banking services; agro-industrial complex; financial support